Axial Load Of Single C-Section Cold Formed Steel With An Opening - Augustine, Deedre (2023)
This paper represented a research on the structural behaviour of cold-formed steel columns affected by local-distortional interaction. Cold-formed steel structural have been widely used in the construction industry and have emerged as a preferred solution for single-storey commercial and industrial building. Commonly, cold-formed steel was manufactured with holes to accommodate plumbing, electrical, and heating conduit in the walls and ceilings of the buildings. This research will be concentrated on the effect of the opening on the C-section cold-formed steel column. The method used for this experiment was compression test which are the column specimens were compressed . Two series of single C-section cold formed steel column will be used in this experiment with opening and without opening .There are three numbers of specimens for each series. Each member has nominal thickness of 1.2 mm and the column length of 600 mm. The displacement of the specimen during testing was read by the transducer. The result of this experiment shows the ultimate load of each specimen varies with the position of the opening and the depth. The graph of load-displacement will studied the movement of the flange during the compression test. The buckling behaviour can be seen along the experiment which is the distortional and local buckling will occur on the specimens. Most of the specimen will failed at the hole.